Detecting Informed Trading Risk from Undercutting Activity - BARARDEHI, YASHAR H.; DIXON, PETER; LIU, QIYU (Journal of Finance, 2026)
ABSTRACT We introduce a simple measure of informed trading risk, , the residual to liquidity quote‐improvement‐to‐deterioration ratio times . When facing with increased informed trading risk, liquidity providers compete less to provide liquidity, reducing their undercutting activity. Reductions in undercutting leave footprints in trade and quote data that are captured by . Unlike prior measures, is easy to construct, can be computed intraday, and is orthogonal to liquidity. The measure outperforms prominent existing alternatives in reflecting the extent of information asymmetry before earnings announcements, predicting unscheduled press releases, and identifying informed trading spillovers around them.